An analysis of the influence of organizational leadership on innovation management using the Fuzzy-AHP method - Wegner, Roger da Silva; Tontini, Julia; Costa, Vânia Medianeira Flores; Muller Junior, Arthur; Silva, Deoclécio Junior Cardoso da (Revista de Administração da UFSM, 2021)
Purpose – The changes that occurred in the market, resulting from technological advancement, made companies pay attention to innovation in their processes, products or services, as a way to stand out. To enhance innovation in companies, focusing on leadership is an effective way. In this sense, the present study aimed to develop a model in order to list the priorities related to leadership and its interface with innovation, under the top management perspective of a telecommunications company. Design/methodology/approach – For the development of the model, the Fuzzy Analytic Hierarchy Process (Fuzzy-AHP) method was used to identify such factors and the best alternatives so that the investigated company can make consistent decisions. Thus, the criteria chosen by the Manager and Director were discovered, as well as the alternatives that they cherish, contributing to the development of innovation within the company. Findings – The results showed that the perception of the two interviewees was similar, however, it is emphasized that they should better choose how to apply innovation within the company. Originality/value – This study opens the way to highlight the importance of the theme of leadership and its interface with innovation for professionals in the management area, favoring decision making, in addition to contributing to the literature, deepening the debate on the theme of leadership and innovation, which is still incipient and needs development.